Prime Decomposition of Three-Dimensional Manifolds into Boundary Connected Sum. (19th February 2014) - Zhang, Meili; Deng, Bo
Abstract : In 2003 Matveev suggested a new version of the Diamond Lemma suitable for topological applications. We apply this result to different situations and get a new conceptual proof of theorem on decomposition of three-dimensional manifolds into boundary connected sum of prime components.